The Visit of a Noble Lady: Elizabeth Craven and Her Account of the Crimea - Nikita Igorevich Khrapunov; Natalia Vitalievna Ginkut (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2018)
This paper analyses a book by Elizabeth Craven, one of the most cited English travelogues of the late 18th century. Today, this epistolary adventure story is considered almost a standard of women’s travelogue. The novel demonstrates the triumph of a charming and brave traveller in the land where barbarianism is mixed with civilization. This book brought resounding success, it was referred to and argued over by contemporaries, and so it is by modern researchers. The Crimea plays an important role in the volume. The authors prove that the letters by Craven underwent considerable editing and some of them were written after her return from the trip. The authors confute the assertion of Russian-speaking scholarship that Craven was an agent who collected confidential information ordered by the secret service of a foreign country. By contrast to most travelogues, Craven draws her readers’ attention on her own figure, making exotic countries nothing but scenery helping the image of the traveller stand out. The analysis demonstrates how the role chosen by the writer determines the author’s strategy, and her principles of collection and presentation of materials. The authors single out the symbols used by Craven to show her “Englishness” in an “uncivilised” environment. Additionally, they demonstrate that as regards facts, Craven’s letters add little to the facts about the Crimea, but contain a great number of stereotypes created by the Westerners in the Age of the Enlightenment. This is the factor determining the place of Craven’s book among other foreign travelogues about the Crimean peninsula. Both from the point of view of its form and content, Craven’s travelogue resembles letters by Charles de Ligne, which were full of fantasies. Finally, the article shows the author’s “hierarchy of civilization” where European culture predominates, with Muslims standing at the lowest level, and Russia occupying an intermediary position and playing the role of a good apprentice of Europeans.